International spillovers from prostitution regulation: The "Nordic model" and sex tourism - Maria Perrotta Berlin; Chiara Latour; Giancarlo Spagnolo (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2023)
We investigate the causal effect of the asymmetric criminalization of prostitution on sex tourism. We exploit legal reforms in five countries that switched from systems where prostitution was legal (Norway, Sweden, Ireland, Canada), or where only buying sex was legal (France), to the "Nordic model" where only buying is criminalized. Using a difference-in-differences approach on data from Google trends and tourism statistics, we estimate the impact of the reforms on tourism flows to neighboring countries and popular sex tourism destinations. We find significant effects for countries where prostitution was legal, but not for France where selling sex was prohibited.
Keywords: D04; I18; J47; K14; K42; 330; Prostitution; Nordic model of prostitution; Regulation; Sex tourism; Google Trends; Policy spillovers